Prenatal exposure to ambient air pollution and autism spectrum disorders: Results from a family‐based case‐control study - Nima Ghahari; Fatemeh Yousefian; Ehsan Najafi (Wiley, 2023)
Abstract Background Autism prevalence has increased considerably, but its etiology is still poorly understood. While there have been suggestions regarding associations between air pollution exposure and neurodevelopmental disorders, several studies have looked at the effect of air pollution exposure on autism. However, the results are inconsistent. The possible role of unknown confounders is mainly blamed for this inconsistency. Methods To minimize confounding effects, we evaluated the impact of air pollution exposure on autism using a family‐based case‐control study. Cases were individuals with a diagnosis of autism born between 2009 and 2012 in Isfahan city, Iran. The controls did not have a previous history of autism and were cousins of the case person. The controls were matched with the autistic cases in terms of residential location and age range. For each trimester of pregnancy, carbon monoxide (CO), nitrogen dioxide (NO2), ozone (O3), sulfur dioxide (SO2), and PM10 exposure were estimated using the inverse distance weighted method. Results The analysis indicates a significant association between CO exposure and autism in the second trimester (OR = 1.59; p = 0.046, 95% CI: 1.01-2.51) and entire pregnancy (OR = 2.02; p = 0.049, 95% CI: 1.01-2.95). Likewise, exposure to NO2 during the second trimester (OR = 1.17; p = 0.006, 95% CI: 1.04-1.31), third trimester (OR = 1.11; p = 0.046, 95% CI: 1.01-1.24), and entire pregnancy (OR = 1.27; p = 0.007, 95% CI: 1.07-1.51) were found to be associated with increased risk of autism. Conclusions Overall, our study found higher exposure to CO and NO2, particularly during the second and third trimesters of pregnancy, was significantly associated with a higher risk of autism.